Lesson - the main form of organizing education - Gozaloy Maqsadbek qizi Semeteyeva; Madina Qodirova; Dildora Sayfullayeva; Superviser: M.M.Mirzakarimova (Science and Education, 2025)
This article highlights the role of the lesson in the educational process, its organizational and pedagogical features, and its didactic significance. It analyzes types of lessons, their structure, main stages, and the requirements for modern lessons. The author presents the lesson as a key tool in developing, educating, and shaping students’ knowledge and skills, and describes ways to improve its effectiveness.